The philosophy of Michael Oakeshott - Nardin, Terry, 1942- (Pennsylvania State University Press, 2001)
"This is the first comprehensive study of Michael Oakeshott as a philosopher rather than a political theorist, which is how most commentators have regarded him. Indeed, the careful reading of his published and unpublished writings that Terry Nardin provides here shows that Oakeshott's concerns have been primarily philosophical, not political. These writings go far beyond politics to offer a critical philosophy of human activity and of the disciplines that interpret and explain it. Oakeshott argues that inquiry can be independent of practical concerns, even when its subject is the thought and action of human beings."--Jacket.